PENGARUH BUDAYA PERUSAHAAN TERHADAP KOMITMEN KARYAWAN PERUSAHAAN PENERBITAN PERS - Ida Ayu Brahmasari (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2008)
Hipercompctition in press industry challenges new publishers to continuously enhance their organizational as well as employees’ commitments. Some studies that have been conducted proved that organizational culture influences organizational as well as employees’ commitments. This research is aimed to prove and analyze the influence of corporate culture that consists of organization values, organization climates and tolerance in risk taking, management support, reward system, attention to detail and orientation to team toward employee commitment of Publisher Company in Surabaya. 95 out of 105 questionnaires distributed were returned and analyzed. The result proved that organization values, tolerance in risk taking, and orientation to team have significant influences toward employee commitment, while organization climates, management support, reward system, attention to detail have no significant influences toward employees’ commitment.